Uma análise do nível de pensamento geométrico segundo modelo de Van Hiele dos alunos no ensino fundamental no bairro Novo II em Barcarena-PA - CORRÊA, Márcia da Silva (2019)
The teaching of Geometry has acquired in recent years, a greater importance in the Senate of educational reforms of the country has been proposed as a fundamental factor of mathematical skills and competences in primary and secondary levels. The objective of this work is through a case study to analyze and detect the level of geometric thinking of the elementary school students, using as main tool the Van Hiele test. With the result obtained from the research we will be able to analyze how the knowledge in geometry of the researched students is.